How Can ‘Health in All Policies’ Help Maximise the Potential of Microbial Biotechnologies for Health, Equity and Sustainability? - Margaret J. Douglas; Liz Green; James Timmis; Timo Clemens; Kenneth Timmis (Microbial Biotechnology)
ABSTRACT Microbial biotechnologies could affect health through multiple pathways, including impacts on food, nutrition, and the physical, economic, and social environment. Health in All Policies is an approach to ensure that plans and policies in all sectors maximise health gains and minimise any health risks. This approach often uses health impact assessment as a structured process to identify and assess positive and negative health impacts and make recommendations to improve these. There are very few examples where HIA has been applied to the implementation of microbial biotechnologies. As more biotechnologies are developed and implemented, more routine use of HIA could help to avoid adverse effects and realise their potential to improve health and reduce health inequalities. This will require greater awareness and understanding of the breadth of links to health, research to build the evidence base for these links, and governance mechanisms to oversee the development and implementation of microbial biotechnologies that prioritise health, equity and sustainability.